2020
DOI: 10.1111/1442-1984.12275
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical recognition in seeds: Germination ofRumex obtusifoliusis promoted by leaves of facilitative adult conspecifics

Abstract: Seeds express various germination behaviors in response to competitor plants. However, germination behaviors in response to facilitator plants are not yet well understood. Rumex obtusifolius seedlings usually appear on the ground near adult conspecific plants, and their survival rate under the canopy of adult conspecifics is higher than that outside the canopy, indicating that adult R. obtusifolius plants facilitate their seedling establishments. We hypothesized that emergence of R. obtusifolius seedlings is p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 53 publications
(69 reference statements)
0
10
0
Order By: Relevance
“…Each individual was separated by at least 2 km. As interspecific competitors, we focused on P. asiatica L., T. repens L. and F. ovina L. These species are the dominant competitors of R. obtusifolius in Japan (Ohsaki et al., 2020). A total of 100 seeds of P. asiatica were collected from two individuals in the field in Aomori Prefecture.…”
Section: Methodsmentioning
confidence: 99%
“…Each individual was separated by at least 2 km. As interspecific competitors, we focused on P. asiatica L., T. repens L. and F. ovina L. These species are the dominant competitors of R. obtusifolius in Japan (Ohsaki et al., 2020). A total of 100 seeds of P. asiatica were collected from two individuals in the field in Aomori Prefecture.…”
Section: Methodsmentioning
confidence: 99%
“…26 , 27 Festuca ovina and P. asiatica are strong competitors of R. obtusifolius : grassland plant communities often shift from being R. obtusifolius dominant to being F. ovina dominant; 28 and, like R. obtusifolius, P. asiatica is a perennial herb that develops a leaf rosette. Leaf chemicals in R. obtusifolius inhibit the germination of F. ovina , 29 and R. obtusifolius may increase them as a competitive response.…”
Section: Resultsmentioning
confidence: 99%
“…This preference for seedlings may be explained by tender leaves with higher nutritive value in young plants and fewer secondary compounds. As leaves mature, the nutrient content declines, excreted salts accumulate on the surface, and leaf toughness increases with metabolic changes in internal fluxes of carbon and minerals (Balakrishnan et al, 2016; Choong, 1996; Elster et al, 1999; Faraco & Lana, 2004; Farnsworth & Ellison, 1991; Ohsaki et al, 2020; Robertson & Duke, 1987; Romero et al, 2006; Roth‐Nebelsick et al, 2001; Saur et al, 1999; Silva et al, 2015; Tiffin, 2002). In another study, Farnsworth and Ellison (1991) found variations in damage between trees and seedlings in Neotropical mangroves (Belize), with higher percentages sometimes occurring in trees.…”
Section: Discussionmentioning
confidence: 99%
“…Plants can be subjected to different levels of herbivory during their development from seed to maturity (Ohsaki et al, 2020; Tiffin, 2002). Studies have shown that herbivores generally cause greater damage to seedlings than to mature plants (Elster et al, 1999; Fenner et al, 1999).…”
Section: Introductionmentioning
confidence: 99%